(1‐Adamantyl)methyl Glycidyl Ether: A Versatile Building Block for Living Polymerization. Issue 11 (28th March 2014) - Moers, Christian; Wrazidlo, Robert; Natalello, Adrian; Netz, Isabelle; Mondeshki, Mihail; Frey, Holger
<x xml:space="preserve">Abstract</x> (1‐Adamantyl)methyl glycidyl ether (AdaGE) is introduced as a versatile monomer for oxyanionic polymerization, enabling controlled incorporation of adamantyl moieties in aliphatic polyethers. Via copolymerization with ethoxyethyl glycidyl ether (EEGE) and subsequent cleavage of the acetal protection groups of EEGE, hydrophilic linear polyglycerols with an adjustable amount of pendant adamantyl moieties are obtained. The adamantyl unit permits control over thermal properties and solubility profile of these polymers (LCST). Additionally, AdaGE is utilized as a termination agent in carbanionic polymerization, affording adamantyl‐terminated polymers. Using these structures as macroinitiators for the polymerization of ethylene oxide affords amphiphilic, in‐chain adamantyl‐functionalized block copolymers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>